Peranan Dinas Perindustrian Dan Perdagangan Dalam Pengembangan Pasar Tradisional Di Kabupaten Gowa (Studi Kasus Pasar Rakyat Sungguminasa) - Muh Wahyudi Mokobombang (JOURNAL OF ADMINISTRATIVE AND SOCIAL SCIENCE, 2022)
The management of traditional markets has the potential to create and expand employment opportunities, especially for workers who lack adequate skills and expertise to work in the formal sector due to their low level of education, and as a place of business, small traders have many strategic values. both from an economic and socio-cultural perspective. The purpose of this study was to determine market management in Gowa Regency, especially the Sungguminasa people's market. The method used in this research is descriptive qualitative. The analysis in this study uses the theory proposed by Henry Fayol with the dimensions of Planning, organizing, commanding, coordinating, controlling. The results showed that the lack of optimal supervision and firmness of the officers regarding the collection of market levies on kiosks and stalls, inadequate facilities and infrastructure, as well as the condition of the narrow market land resulted in street vendors not being accommodated. Lack of ineffective placement personnel became an inhibiting factor in socialization process to traders. The researcher's suggestion is that the Gowa Regency Industry and Trade Department should fix the market effectively and efficiently and increase market optimization, it is necessary to take steps to improve the quality and quantity of human resources and other supporting resources, so that traders are placed in appropriate places and it is hoped that the Gowa Regency Industry and Trade Department will pay more attention to the facilities provided. is around the market.